Building the Eiffel Tower [videorecording (DVD)] - Cuissot, Pascal; Kessler, Simon; Guinet, Nathalia; Glimois, Nicholas; Boffey, Mercer, 1982- (PBS, 2024)
Explore the revolutionary engineering behind Paris's iconic landmark. Completed in just over two years for the 1889 World's Fair, the iron tower smashed the record for the tallest structure on Earth, ushering in a new age of global construction that reached for the skies. How did the engineers do it?